APPLICATION PROGRAM ON PC WITH PROTECTION METHOD USING VISUAL BASIC 6.0 CRYPT - Lisa Trisia; Don Elsyafitra, Ir, SKom (Jurnal Sistem Informasi, 2002)
Writing consists of four chapters, where the first chapter explains the background ofproblems in the importance of maintaining the security of data so that the data wehave can not be viewed or manipulated by others.On the second chapter, the authors make a basic theories used to solve the problem inthe first chapters. Besides there are also explanations on the types of programs used toassist writers in completing the problems with computer.Analysis of problems and their solutions are explained in the third chapter, where anexplanation of the method and how to solve the problem were performed using themethod described in previous chapters. Here are given also how to run the program,explanation of the program that the author made and the design of its output.The conclusion of this chapter is contained in chapter four is that of a data security isimportant, even more so on the current era of computerization, where the use ofcomputers as a tool of man in completing the work is felt to increase.